2014
DOI: 10.1063/1.4894843
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and versatile applications of low hydrogen content SiOCN grown by plasma-enhanced chemical vapor deposition

Abstract: Low hydrogen content silicon oxycarbonitride (SiOCN) thin films were grown by plasma-enhanced chemical vapor deposition exploiting hydrogen dilution with silane/methane/nitrous oxide or tetramethylsilane/nitrous oxide precursors. The effects of deposition temperature were compared by investigating the compositional, optical, mechanical, and electrical properties of films grown at 100 °C, 250 °C, and 400 °C at thicknesses ranging from 50 nm to 10 μm. The dielectric constant and high breakdown strength of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 74 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…P-type silicon (001) substrates were chosen for all experiments except for Rutherford backscattering spectrometry (RBS) where glassy carbon wafers were employed to improve the sensitivity for light elements. The adhesion quality of SiCN thin films deposited on silicon substrates was found to be better than on glass substrates, likely due to a smaller difference in the coefficient of thermal expansion between the SiCN film and the substrate [21].…”
Section: Sample Fabricationmentioning
confidence: 96%
See 1 more Smart Citation
“…P-type silicon (001) substrates were chosen for all experiments except for Rutherford backscattering spectrometry (RBS) where glassy carbon wafers were employed to improve the sensitivity for light elements. The adhesion quality of SiCN thin films deposited on silicon substrates was found to be better than on glass substrates, likely due to a smaller difference in the coefficient of thermal expansion between the SiCN film and the substrate [21].…”
Section: Sample Fabricationmentioning
confidence: 96%
“…It is worth mentioning that polymer-derived SiCN ceramics, which require higher pressure and temperature processing [20], are not of interest for silicon photonics. The mechanical aspects of SiCN thin films processed using existing CMOS compatible technology were investigated in various works [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen being a diatomic light gas can easily diffuse through any material while carrying out the synthesis process. Thus, increase in H 2 flow rate had resulted in (a) improving the hardness (b) reducing the wear rate and friction coefficient of the SiCN thin film [6,7]. Sundaram et al [8] found an increasing trend of hardness and young's modulus values of the SiCN thin films with an increase in the nitrogen flow rate.…”
Section: Introductionmentioning
confidence: 99%